Peningkatan Kapasitas Analisis Data Sebagai Strategi Penguatan SDM Berbasis Evidence-Based Decision Making - Yunita, Mela; Setiyantono, Aulia Pamasa (Universitas Muhammadiyah Mataram, 2026)
Abstract: Data analysis skills have become a crucial aspect of strategic decision-making in the fields of modern economics and business. However, only a limited number of people have mastered this skill. This data analysis training aims to enhance the analytical capacity of students and business practitioners in responding to the challenges of datadriven decision making. The activity was conducted as a technical training session using a handson approach with the STATA statistical software. The target participants included final-year university students and business practitioners who require an understanding of data structures and their application in economic and business studies. Evaluation results indicate a significant improvement in participants' conceptual understanding and technical skills. This outcome contributes to strengthening managerial capacity and fostering databased decision making. Moreover, the program supports the development of data analysis expertise and human resource development in both the business sector and higher educationAbstrak: Keterampilan analisis data telah menjadi aspek penting dalam pengambilan keputusan strategis di bidang ekonomi dan bisnis modern. Namun, hanya sebagian kecil orang yang menguasai keterampilan ini. Pelatihan analisis data ini bertujuan untuk meningkatkan kapasitas analitis mahasiswa dan praktisi bisnis dalam menanggapi tantangan pengambilan keputusan berbasis data. Kegiatan ini dilakukan sebagai sesi pelatihan teknis menggunakan pendekatan praktik langsung dengan perangkat lunak statistik STATA. Peserta sasaran meliputi mahasiswa tingkat akhir dan praktisi bisnis yang membutuhkan pemahaman tentang struktur data dan penerapannya dalam studi ekonomi dan bisnis. Hasil evaluasi menunjukkan peningkatan yang signifikan dalam pemahaman konseptual dan keterampilan teknis peserta. Hasil ini berkontribusi pada penguatan kapasitas manajerial dan mendorong pengambilan keputusan berbasis data. Selain itu, program ini mendukung pengembangan keahlian analisis data dan pengembangan sumber daya manusia baik di sektor bisnis maupun pendidikan tinggi.